Risk Mitigation Design for Supply Chain Activities in Printing Industry with House of Risk Method - Suaib, Robih Alfian Hastrianda; Mansur, Agus; Basuki, Demas Emirbuwono; Aulia, Baiq Putri Rizka (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Alvian MSMEs is a company engaged in printing, which serves ordering calendars, banners or billboards. The problem faced by Alvian MSMEs today is supply chain activities and production that are usually late so that products experience a decrease in buying interest from customers. To overcome these problems, MSMEs mitigate risks in supply chain and production activities using the HOR (House Of Risk) Method. Based on Hor phase 1, 12 risk events and risk agents were obtained. The identification results show that the highest risk agent is low-quality raw materials (A9). This risk agent has the highest value because it can cause risk events in the form of poor quality or defects (E9). In HOR phase 2, 6 priorities were obtained for risk mitigation to prevent system failure (PA3), implementing preventive maintenance routines is a top priority. With an ETDk value of 10386, PA3 mitigation measures can reduce risk factors such as manufacturing defects, misconceptions of customer specifications, and quality testing problems, improper maintenance, overuse, system failure, technical problems with printing machines, staff or management failures, no routine monitoring of machine checks (A11,A8,A4,A5,A7).